Testing the Fama and French three factor model : evidence from China - Ho, Qiao Yi (2010)
The objective of the study is to examine the performance of the Fama and French three factor model in explaining the average cross-sectional returns in China stock market. The market, consisting of the Shanghai and Shenzhen stock exchange, is uniquely characterized by individual investors who based their investments on market rumours. We tests the daily and monthly stock returns against the Fama-French three factors, namely excess market return, firm size and book-to-market ratio. Our findings reflect that the three factors on the daily data were found to have significant explanatory power, consistent with Fama and French’s (1992) findings. However, when using monthly data, the firm size factor was found to be insignificant in explaining the big firm portfolios’ returns. In addition, we found that the regression of the Fama-French three factors on the monthly data shows significant improvements in explanatory power in comparison to CAPM, particularly for the small size portfolios.